Dampak Tema Alam dalam Kafe pada Brand Experience dan Active Engagement - Tjokro, Nicholas Hugo; Fernando, Vicky; Yosevina, Christiana Tercina; Amelia, Novi (Universitas Prasetiya Mulya, 2025)
This study aims to investigate the impact of nature-themed cafes on brand experience and Active engagement. The research employs a quantitative method with online questionnaires distributed to visitors of nature-themed cafes in Tangerang. The results indicate that positive brand experiences in nature-themed cafes significantly enhance customer engagement and brand loyalty. The practical implications of this study highlight the importance for cafe managers to focus on creating enjoyable and engaging experiences to boost customer loyalty and achieve sustainable competitive advantages.